A COMPARATIVE STUDY OF YARN DYED WASTEWATER USING FENTON’S REAGENT AND OZONATION : REMOVAL EFFICIENCY AND ECONOMIC ANALYSIS - Lieke Riadi; Richard Wisanto; Arief Rachmat Herlambang; Sasmita Mirifica Vania; Andy Widyasayogo (Dept. of Chemical Engineering, Diponegoro University, 2016)
This study makes a comparison between Fenton and Ozonation processes treatment methods to examine the removal of COD in yarn dyed wastewater with initial concentration of 525 ppm. Results indicated that the COD degradation efficiency was in order of Fenton > Ozone. In Fenton method, the ratio of Fe2+/H2O2 used was 1 :10, the concentration of H2O2 was 10.2 gram/L. In ozonation, the ozone concentration used in the study was 5.8 % mol, and the agitation was 400 rpm. The effect of operational parameters including, initial pH and time were studied in both processes. The results indicated that it was 86.2 % COD were removed, when the pH was about 3 using Fenton’s reagent and 83.06 % COD removal in ozonation for one hour experiment. To achieve the standard requirement for allowable parameters in wastewater to be discharged, there is only 15 minutes needed for Fenton process to remove COD by 84.8 %, while the ozonation needs 30 minutes for 81 %removal. Fenton process is more economic feasible compare to ozonation which is almost one-tenth of the operation cost for 1 liter of wastewater being process. Though both processes can demonstrate the high removal efficiency to achieve the allowable COD concentration in the wastewater to be discharged, Fenton process is favor to ozonation.